Signals Sell: Product Lines when Consumers Differ Both in Taste for Quality and Image Concern - Jana Friedrichsen (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
This paper analyzes optimal product lines when consumers differ both in their taste for quality and in their desire for social image. The market outcome features partial pooling and product differentiation that is not driven by heterogeneous valuations for quality but by image concerns. A typical monopoly outcome is a two-tier product line resembling a m̈asstiges̈trategy as observed in luxury goods markets. Products can have identical quality and differ only in price and image, thereby rationalizing quality-equivalent line extensions. Under competition, both average quality and market coverage are (weakly) higher but monopoly can yield higher welfare than competition.
Keywords: L12; L15; D11; D21; D82; 330; image concern; conspicuous consumption; two-dimensional screening; nonlinear pricing